Types and sentences structure charged with character education values essays of grade IV elementary school students in Bali Province: A syntactic study - Putrayasa, Ida Bagus (Linguistics and Culture Review, 2023)
The main objective of this descriptive-qualitatively designed study is to describe (1) types of sentences and (2) sentence structures based on character education values contained in the essays of grade IV elementary school students in Bali province. The subject of this study is the essay of grade IV elementary school students in Bali province, while the objects are (1) types of sentences and (2) sentence structures based on character education values contained in the essays of grade IV elementary school students in Bali province. Data is collected by the method of recording documents. Furthermore, the collected data are analyzed descriptively-qualitatively. The results showed that: (1) the types of sentences contained in the essays of grade IV elementary school students in Bali province can be divided based on (a) the number of clauses, there are 804 single sentences, 494 compound sentences, (b) the internal structure of the main clause, there are 1209 complete sentences and 89 incomplete sentences. (2) The sentence structure, both single and compound, contained in the essays of grade IV elementary school students in Bali province is quite varied.